Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
bài 2
\(2^x\cdot7=224\)
\(\Rightarrow2^x=224\div7\)
\(\Rightarrow2^x=32\)
\(\Rightarrow2^x=2^5\)
\(\Rightarrow x=5\)
\(\left(3^x+5\right)^2=289\)
\(\Rightarrow\left(3^x+5\right)^2=17^2\)
\(\Rightarrow3^x+5=17\)
\(\Rightarrow3^x=17-5\)
\(\Rightarrow3^x=12\)
a) \(2^{x+2}-2^x=96\)\(\Leftrightarrow2^x.4-2^x=96\)
\(\Leftrightarrow2^x\left(4-1\right)=96\)\(\Leftrightarrow2^x.3=96\)\(\Leftrightarrow2^x=32=2^5\)
\(\Leftrightarrow x=5\)
Vậy \(x=5\)
b) \(10^6-5^7=\left(2.5\right)^6-5^{6+1}=2^6.5^6-5^6.5=5^6\left(2^6-5\right)=5^6\left(64-5\right)=5^6.59⋮59\)
c) \(81^7-27^9-9^{13}=\left(3^4\right)^7-\left(3^3\right)^9-\left(3^2\right)^{13}=3^{28}-3^{27}-3^{26}\)
\(=3^{24}\left(3^4-3^3-3^2\right)=3^{24}\left(81-27-9\right)=3^{24}.45⋮45\)
1. Ta có: 2x + 2 - 2x = 96
=> 2x.4 - 2x = 96
=> 2x(4 - 1) = 96
=> 2x = 96 : 3
=> 2x = 32
=> 2x = 25
=> x = 5
2. Ta có: 106 - 57 = (2.5)6 - 57 = 26.56 - 56.5 = 56(64 - 5) = 56 . 59 \(⋮\)59
817 - 279 - 913 = (34)7 - (33)9 - (32)13 = 328 - 327 - 326 = 324.(34 - 33 - 32) = 224. 45 \(⋮\)45
1/4+2/5+6/8+2/15+6/7
=(1/4+6/8)+(2/5+2/15)+6/7
=(2/8+6/8)+(6/15+2/15)+6/7
=1+8/15+6/7
=1+56/105+90/105
=1+146/105
=1+105/105+41/105
=1+1+41/105
=2+41/105
=2 và 41/105
2 và 41/105 là hỗn số nha
1/4+2/5+6/8+2/15+6/7
Ta có:
1/4=1-3/4
6/8=3/4
2/15=2/3*5=1/3-1/5
==> 1-3/4+2/5+3/4+1/3-1/5+6/7
=1+1/3+1/5+6/7
=(105+35+21+90)/105
=251/105.
\(a,2x+15=27\)
\(\Rightarrow2x=27-15\)
\(\Rightarrow2x=12\)
\(\Rightarrow x=12\div2\)
\(\Rightarrow x=6\)
a/ 2x . 7 = 224
2x = 224 : 7
2x = 32
2x = 25
x = 5.
b/ 32x + 1 . 11 = 2673
32x + 1 = 2673 : 11
32x + 1 = 243
32x + 1 = 35
32x = 35 - 1
32x = 34
2x = 4
x = 4 : 2
x = 2.
c/ (3x + 5)2 = 289
(3x + 5)2 = 172
3x + 5 = 17
3x = 17 - 5
3x = 12
x = 12 : 3
x = 4.
d/ x . (x2)3 = x5
x1 . x5 = x5
x6 = x5
=> x = 0 hoặc x = 1
a) 2x x 7=224
2x=224:7
2x=32
2x=25
=> x=5
Vậy x=5
b) 32x+1 x 11=2673
32x+1=2673:11
32x+1=243
32x+1=35
=> 2x+1=5
x=(5-1):2
x=2
Vậy x=2
c) (3*x+5)2=289
(3*x+5)2=172
=> 3*x+5=17
x=(17-5):3
x=4
Vậy x=4
d) x.(x2)3=x5
x.x6=x5
x=x5:x6
x=x-1
a) -5(x - 3) - 2(5 - 3x) = -(x - 1)
=> -5x + 15 - 10 + 6x = -x + 1
=> x + 5 = -x + 1
=> x + x = 1 - 5
=> 2x = -4
=> x = -4 : 2
=> x = -2
\(-5\left(x-3\right)-2\left(5-3x\right)=-\left(x-1\right)\)
\(\Leftrightarrow-5x+15-10+6x=-x+1\)
\(\Leftrightarrow x+5=1-x\)
\(\Leftrightarrow2x=-4\)
\(\Leftrightarrow x=-4\div2\)
\(\Leftrightarrow x=-2\)
a) ( x + 3 )3 : 3 - 1 = -10
( x + 3 )3 : 3 = -10 + 1
( x + 3 )3 = -9 * 3
x + 3 = \(\sqrt[3]{-27}\)
x = -3 - 3
x = -6
b) 3 | x - 1 | + 5 = 17
3 | x - 1 | = 17 - 5
| x - 1 | = 12 : 3
| x - 1 | = 4
( 1 ) x - 1 > 0 => x - 1 = 4 => x = 5
( 2 ) x - 1 < 0 => x - 1 = -4 => x = -3
Vậy S = { -3 ; 5 }
h. (3x + 5)2 = 289 => 3x + 5 = 17 hoặc 3x + 5 = -17
3x = 17 - 5 = 12 hoặc 3x = -17 - 5 = -22
x = 12 : 3 = 4 hoặc x = -22 : 3 = -22/3
Vậy x = 4 hoặc -22/3
g. 2x . 7 = 224 => 2x = 224 : 7 = 32 => x = 5
Vậy x = 5